The functions of bayas in bodong celebration among the Kalingas - Bulwayan, Ronald B. (KSU Research Journal, 2019)
The study looked into the functions of bayas in the bodong celebration of the Kalingas. It made use of the ethnographic method, specifically interviews with the elders and bodong holders. Actual photo-documentation was also used to capture essential procedures of the rituals. It found out of that bayas is used as a major ingredient and material necessary necessary in a badong celebration. Specifically, the bayas suggests welcome for visitors, show of acceptance and accommodation in the community, acknowledging the presence of elders and agreement or approval of the pagta. It was also noted that the use and implications of bayas in Kalinga celebrations relate to religious beliefs and scientific explanations.